Feasibility Study On Igg Network Development In The Sangatta & Mangkajang Branching Unit Using Mp?s - Bima Kurnia Marahsakti A. Karel; Erna Sri Sugesti; Ahmad Tri Hanuranto (eProceedings of Engineering, 2020)
Abstract. The province of East Kalimantan has good market potential, due to the relocation of Indonesia’s capital city to East Kalimantan. Based on the results of population projections, it is estimated that in 2040 the population in East Kalimantan will reach 189.917.791 inhabitants. Unfortunately, there is only one landing station that connects East Kalimantan with the internet network, the Balikpapan landing station. This study conducted an analysis of the placement of landing station based on potential internet users, geographical conditions, network feasibility based on the value of Bit Error Rate (BER), Quality Factor (Q-Factor), Power Received, and business feasibility by the Net Present Value (NPV), Internal Rate of Return (IRR), and Payback Period (PBP). The technical simulation result showed BER value 3,94E-32, Q-Factor 11,7147, and power received -18,8614 dBm. Besides, for Capital Budgeting simulation results show that it takes 4 years 3 months for the PBP, NPV > 0 and, IRR of 31 %. Keywords: Submarine Cable Network, Net Present Value, Internal Rate of Return, Payback Period, Indonesia Global Gateway (IGG).